PENGARUH PENDAFTARAN MEREK DAGANG TERHADAP PENINGKATAN PENJUALAN INDUSTRI RUMAH TANGGA DI MASA PANDEMI COVID-19 - Heriyanti, Yuli (Jurnal Teknik Industri Terintegrasi (JUTIN), 2020)
Home industry is an example of business and is the livelihood of the general public in Indonesia. This can be found in every region in Indonesia which has a home industry which is generally a regional specialty food or drink. As a home industry that is hereditary makes this business does not develop. This is caused by the marketing system that is still traditional and the community's lack of knowledge about the development of information technology. This online media has never been utilized by businesses in terms of developing the selling power of their products. The development of information technology at this time finally paid off with the growing popularity of home-based products and typical Indonesian food to the corners of the world. Some typical foods that are marketed have a variety of mentions in each region with the same ingredients. The variety of names makes the need for a brand that can identify the product. The brand will give more value to the product because with the brand, businesses can collaborate with third parties to market their products. With the Law No. 20 of 2016 concerning Brands and Geographical Indications and electronic commerce as well as training on the use of information technology to the general public will facilitate in terms of increased revenue, time efficiency both for production, marketing and sales processes.